PENGARUH KOMUNIKASI, KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP SEMANGAT KERJA KARYAWAN PADA AIRPORT SERVICES DAN HOSPITALITY OFFICER DI BANDAR UDARA INTERNASIONAL I GUSTI NGURAHRAI BALI - Kadek Ika Silvia Dewi; Ni Putu Yeni Astiti; I Nyoman Resa Adhika (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
Spirit at work is a term used to describe the activities that are aimed to boast the productivity at work, there are some factors that play important rule such as: communication between team and team leader, compensation and safe and secure working environtment.The porpuse of this study is to find out whether or not those factors (comunication, compensation, and secure working environment) can improve significantly the spirit at work of Airport Services and Hospitality Officer at Bali I Gusti Ngurah Rai Internasional Airport. The result of the study shows that communication (X1) gives positif and significant impactto the spirit at work of the employee (Y), compensation (X2)gives positif and significant impact tothe spirit at work of the employee (Y), safe and secure working environment (X3) gives positif and significant impact to the spirit at work at the employee (Y).